ELASTIC AND INELASTIC TRIGGERING OF EARTHQUAKES IN THE NORTH ANATOLIAN FAULT ZONE - Lorenzo-Martín F.; Roth F.; Wang R. (My University, 2006)
Deformation models used to explain the triggering mechanism often assume pure elastic behaviour for the crust and upper mantle. In reality however, the mantle and possibly the lower crust behave viscoelastically, particularly over longer time scales. Consequently, the stress field of an earthquake is in general time-dependent. In addition, if the elastic stress increase were enough to trigger a later earthquake, this triggered event should occur instantaneously and not many years after the triggering event. Hence, it is appropriate to include inelastic behaviour when analysing stress transfer and earthquake interaction.